The Sling and the Stone : On War in the 21st Century - Hammes, Thomas X. (GHQ, Rawalpind Army Education Publishing House, 2013)
Ongoing events in Iraq show how difficult it is for the world's only remaining superpower to impose its will upon other peoples. From Vietnam, French and US, to Afghanistan, Russian and US, to Israel and the Palestinians, to Somalia and Kosovo, recent history is replete with powerful military forces being tied up by seemingly weaker opponents. This is Fourth Generation War (4GW), and Colonel Thomas Hammes, United States Marine Corps, tells you all about it. The author explains asymetrical warfare (4GW) as the means by which Davids can defeat Goliaths. Answers to the "hows" of this along with recommendations for prescriptive actions are found in Thomas Hammes insightful book on the strengths and weaknesses of conventional military power. Hammes, a full colonel on active duty in the Marine Corps is an expert at asymetrical warfare, perhaps better known as fourth generation warfare (4GW). This is the means by which Davids can defeat Goliaths. Colonel Hammes is well placed to write this study. As a career-Marine he has trained 4GW warriors in some places and fought against them in others.
Include Notes, References and Index
Keywords: Counterinsurgency -- Asymmetric Warfare -- Operational Art (Military science)